2012
DOI: 10.1002/jat.2834
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to low concentrations of strontium 90 affects bone physiology but not the hematopoietic system in mice

Abstract: The aim of this work was to delineate the effects of chronic ingestion of strontium 90 ((90) Sr) at low concentrations on the hematopoiesis and the bone physiology. A mouse model was used for that purpose. Parent animals ingested water containing 20 kBq l(-1) of (90) Sr two weeks before mating. Offspring were then continuously contaminated with (90) Sr through placental transfer during fetal life, through lactation after birth and through drinking water after weaning. At various ages between birth and 20 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
(78 reference statements)
2
9
0
1
Order By: Relevance
“…These observed effects remains limited in range but such changes in 90 Sr-exposed BMSCs accumulated in bone tissue may explain some of the previously observed health effects of chronic 90 Sr ingestion. In fact, we previously observed a change in bone physiology towards bone resorption 9 and a modification in immune response that could be linked to B cell differentiation in the bone marrow 10 . Additionally, studies in humans suggested decreased hematopoiesis and an altered immune status after internal contamination with 90 Sr together with a decreased bone remodeling rate 7 8 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These observed effects remains limited in range but such changes in 90 Sr-exposed BMSCs accumulated in bone tissue may explain some of the previously observed health effects of chronic 90 Sr ingestion. In fact, we previously observed a change in bone physiology towards bone resorption 9 and a modification in immune response that could be linked to B cell differentiation in the bone marrow 10 . Additionally, studies in humans suggested decreased hematopoiesis and an altered immune status after internal contamination with 90 Sr together with a decreased bone remodeling rate 7 8 .…”
Section: Discussionmentioning
confidence: 97%
“…A decreased bone remodeling rate was also observed in this population 8 . In addition, we demonstrated an increased bone resorption 9 and a reduced immune response to a vaccine challenge 10 in mice exposed to 90 Sr through ingestion for 20 weeks. However, the mechanisms underlying these health effects remain unclear.…”
mentioning
confidence: 81%
“…So nuclear waste contains lots of 90 Sr. 90 Sr could launch β rays, and its half-life reaches 28.6 years [2,3]. 90 Sr with its long half-life is considered to be the critical isotope tend to be strongly retained within the living organisms such as bones [4]. Therefore 90 Sr is a contamination that must be removed.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer incidence has also been studied in mice exposed to 90 Sr as an internal emitter, and no tumors were observed below a cumulative average bone dose of 18 Gy [ 18 ], suggesting that structural and cellular effects on bone and hematopoietic functions may be the highest risks from internal contamination by 90 Sr in mice [ 19 22 ]. Other mouse studies have reported 90 Sr effects including altered gene expression and cellular changes in bone cells [ 20 , 22 , 23 ]. These studies explored the effects of strontium ingestion, and therefore chronic exposure, in BALB/c mice, with a maximum dose of 10 mGy at the end of a 20-week study; and it was found that these doses affected bone morphogenesis, but not hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%